The effect of conjugated π-bridge and fluorination on the properties of asymmetric-building-block-containing polymers (ABC polymers) based on dithienopyran donor and benzothiadiazole acceptors. Issue 35 (10th August 2017) - Wang, Xiaochen; Tang, Ailing; Chen, Fan; Zhou, Erjun
Abstract : Inserting a hexylthiophene bridge betweenDTPa andBTs significantly reduced the intramolecular charge transfer and consequently affected the properties of the resultingABC polymers. Abstract : To investigate the effect of conjugated π-bridge and fluorination on the properties of asymmetric-building-block-containing polymers (ABC polymers), hexylthiophene(HT) was inserted into D–A-type polymers based on asymmetric dithieno[3, 2- b :2′, 3′- d ]pyran (DTPa ) donor and benzothiadiazole (BT ), mono-fluorinated benzothiadiazole (fBT ) or di-fluorinated benzothiadiazole (ffBT ) acceptors, respectively. In comparison with non-bridged analogs, introducing theHT π-bridge betweenDTPa andBTs significantly reduced the intramolecular charge transfer and consequently affected the absorption spectra, frontier energy levels, and electrochemical and charge transport properties of the resultingABC polymer s. Interestingly, HT π-bridge enlarged the fluorination effect on photovoltaic properties, and the power conversion efficiency (PCE) increased gradually from 1.56% (DTPa-HTBT ) to 4.39% (DTPa-HTfBT ) and 6.09% (DTPa-HTffBT ), significantly different with non-bridged polymers. Most importantly, with the increase in the number of the fluorine atoms on theBT unit, all of the photovoltaic parameters, including PCE, V oc, J sc, and FF, improved gradually, which provides a useful guide for the further design ofABC photovoltaic polymers.